Toolkit for the efficient articulation of sustainable strategies with design and management methodology used by AECO industry in Latin America - Carolina Valbuena-Bermúdez; Claudia Bengoa-Alvarez (Acta Polytechnica CTU Proceedings, 2022)
Digital transformation is changing the world, and with it the construction and architecture industry, however, although there are many collaborative work frameworks for digitization, and agile philosophies among different professionals, the methodologies of creative processes throughout the entire life cycle of a project that involves sustainability strategies have been greatly reduced and relegated over time. Latin America has the highest levels of biodiversity, a wide variety of climates, a~range of implementations and sustainable opportunities that have been sidelined versus the speed of innovation in construction projects, in this context, the design philosophy based on nature must be implemented as a premise from leaders to developers, regardless of the management method used. This document studies the sustainable construction progress in five Latin American countries, analyzing climatic, regulatory and socioeconomic aspects, with the aim of increasing processes efficiency towards better sustainable constructions. Consequently, it proposes a methodology for the creation of an effective sustainable tool which works hand in hand with information systems and synchronous digital collaboration (BIM, VCD or IPD), in order to improve the design and management of sustainable projects throughout their life cycle through specific design strategies and design guidelines for each city, using the cities of Buenos Aires, Brasilia, Santiago, Bogotá and Lima as a case study.